1990
DOI: 10.1111/j.1432-1033.1990.tb19114.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the fluidity of lipopolysaccharide and free lipid A membrane systems by Fourier‐transform infrared spectroscopy and differential scanning calorimetry

Abstract: The phase behaviour, particularly the fluidity within each phase state and the transitions between them, of lipopolysaccharides and of their lipid moiety, free lipid A, of various species of Gram-negative bacteria, especially of Salmonella minnesota and Escherichia coli, has been investigated by applying mainly Fourier-transform infrared spectroscopy and differential scanning calorimetry. For enterobacterial strains, the transition temperatures of the gel-liquid crystalline (P-cI) phase transition of the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 33 publications
8
80
0
Order By: Relevance
“…Moreover, the same effects could explain the increase in acyl-chain fluidity observed for the LPS of Y . pseudotuberculosis grown at 37 "C. However, as phase transitions have been observed for R LPSs of enterobacteria under conditions similar to those used in this study (Brandenburg & Seydel, 1984, 1990 In a previous study we have shown that the OMS of Y . enterocolitica pathogenic biogroups, but not those of non-pathogenic biogroups, become permeable to hydrophobic agents when grown with Mg2+ but no Ca2+ available (Bengoechea et al, 1996).…”
Section: Lps-lps Interactions the Reduced Hydration Of Re Orsupporting
confidence: 61%
See 1 more Smart Citation
“…Moreover, the same effects could explain the increase in acyl-chain fluidity observed for the LPS of Y . pseudotuberculosis grown at 37 "C. However, as phase transitions have been observed for R LPSs of enterobacteria under conditions similar to those used in this study (Brandenburg & Seydel, 1984, 1990 In a previous study we have shown that the OMS of Y . enterocolitica pathogenic biogroups, but not those of non-pathogenic biogroups, become permeable to hydrophobic agents when grown with Mg2+ but no Ca2+ available (Bengoechea et al, 1996).…”
Section: Lps-lps Interactions the Reduced Hydration Of Re Orsupporting
confidence: 61%
“…The variations in LPS acyl-chain fluidity (and the concomitant variations in LPS-LPS interactions) must have a structural explanation. Since electrostatic and/or hydrophilic interactions between polysaccharide moieties of LPSs can decrease the overall LPS fluidity (Brandenburg & Seydel, 1984, 1990) and the LPS polysaccharide length decreased in the order Y . enterocolitica-Y.…”
Section: Lps-lps Interactions the Reduced Hydration Of Re Ormentioning
confidence: 99%
“…This can be interpreted in part to result from the reaction between the divalent cations and the negatively charged groups, mainly the phosphate groups of the disaccharide moiety of lipid A. Indeed, this should rigidify the structure of LPS to a higher degree than that of LPS with longer sugar chains, to which Mg 2ϩ cations can distribute over a much larger region (64), also increasing the volume occupied by water molecules, in a disordered assembly (63).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the study of the latter system gives us some interesting pieces of information. In more recent studies (89,604), it was shown that Mg 2ϩ raises the melting temperature of lipid A. Furthermore, the melting temperature of lipid A measured by Fourier transform infrared spectroscopy was about 57°C, in comparison with that of dioleoylglycerophosphate (about 3°C) (89), showing clearly that lipid A hydrocarbons are in a much more strongly ordered state.…”
Section: What Makes the Lps Leaflet An Effectivementioning
confidence: 95%